In vitro growth response and acclimatization performance of chitosan treated hermaphrodite papaya (carica papaya L. cv. Eksotika) - Lee, Sin Yee (2014)
In vitro propagation of papaya has been reported to be hindered by slow explant initiation and proliferation as well as the production of abnormal shoots and roots which resulted in low plantlets survival rate during transplantation. Chitosan supplementation to culture media and through foliar application has been reported to give positive effects on in vitro growth and ex vitro acclimatization of several crop species. The present study aims at establishing a complete and reliable method of propagation of hermaphrodite papaya (Carica papaya L. cv. Eksotika) through the determination of best sterilization procedure, type of explant, medium and plant growth regulators (PGRs) requirements, the application of chitosan to improve in vitro shoot and root growth and plantlets performance during ex vitro acclimatization. In attempts to minimize the possible variations, a single mother plant was used as source of planting material throughout the study. This is the first report on the application of chitosan on Eksotika papaya. Explants taken from greenhouse mother plant and treated with 20% NaOCl solution for 20 minutes experienced low percentage of explant contamination (35.20%) with comparatively high rate of explant viability (74.67%). Shoot tip was identified as the suitable planting material with higher percentage of explant viability (73.33%). Full-MS salt was superior to half-MS in shoot growth and development. The combination of 1.0 mg L-1 BAP and 0.1 mg L-1 NAA was selected as the basal plant growth regulators for experiment with chitosan application based on its maximum performance on shoot proliferation. The treatment induced shoot after 13 days of culture, resulted in highest rate of proliferation (128.9 shoots per explant) and an average shoot height of 1.96 cm. Chitosan supplementation had significantly enhanced growth and development of papaya shoot tip explants. Chitosan at 20 mg L-1 induced earliest shoot initiation which occurred after seven days of culture. This was six days earlier than control treatment. Treatment with 15 mg L-1 chitosan resulted in maximum rate of shoot proliferation (220 shoots per explant). This was approximately two-fold higher than control. Longest shoots (4.18 cm) were obtained on medium supplemented with 5 mg L-1 chitosan. Chitosan application enhanced in vitro rooting and acclimatization of papaya. Half-MS was superior to full-MS in papaya rooting procedure. Earliest root induction was observed on half-MS with 1.0 mg L-1 IBA and 15 mg L-1 chitosan after nine days of culture. Half-MS with 1.0 mg L-1 IBA and 5 mg L-1 chitosan recorded highest mean number of roots per explant (8.00). Longest roots (7 cm) were produced on half-MS supplemented with 1.0 mg L-1 IBA and 5 mg L-1 chitosan. Foliar application of chitosan at 30 mg L-1 resulted in highest survival percentage (93.33%) and maximum mean difference of shoot growth (11.33 cm) of the resultant plantlets during ex vitro acclimatization. In conclusion, the present study showed that the addition of chitosan had profound effects on in vitro growth performance and ex vitro acclimatization of papaya explants. It offers the potential use of chitosan to overcome the shortcomings in in vitro culture of papaya.